AGRESIVITAS PAJAK DARI SUDUT PANDANG MANAJEMEN LABA - Machdar, Nera Marinda (Economic Faculty, Attahiriyah Islamic University, 2019)
The tax collected by the government utilizes to finance the state and regional expenses. In Indonesia, the realization of tax revenues is always smaller than the planned tax revenue set by the Government. This is probably because many companies carry out earnings management so that the taxes paid are aggressive. The purpose of this study is to examine the effect of earnings management on tax aggressiveness. This study uses a sample of manufacturing companies as an analysis unit listed on the Indonesia Stock Exchange (IDX) during the 2011–2016 observation period. This study found some of the following: first, accrual earnings management has a positive effect on tax aggressiveness. Second, real earnings management has a positive effect on tax aggressiveness. Third, the liquidity control variable tested does not affect tax aggressiveness. Keywords: Earning Management, Real Earning Management, Tax Aggressiveness